Epistemic bias and the rise of qualitative dominance in post-authoritarian Indonesian communication research - Adiprasetio, Justito (Frontiers in Communication, 2025)
The field of communication studies has long been defined by deep epistemological divisions between quantitative and qualitative traditions. These divides are not merely intellectual disagreements; rather, they are deeply entangled with the history of knowledge imperialism, the politics of knowledge production, and contemporary efforts toward knowledge decolonization. In several contexts, efforts to decolonize knowledge have produced unintended consequences, including new forms of epistemic imbalance. This tension is particularly evident in countries like Indonesia, where the legacy of Cold War geopolitics and decades of authoritarian rule continue to shape academic practices. Following the country’s political transition and the liberalization of higher education, interpretive and critical paradigms began to gain ground in communication scholarship. Central to this shift were the contributions of Dedy N. Hidayat and Deddy Mulyana. Hidayat’s work on the political economy of communication challenged the technocratic and instrumentalist foundations of earlier research, while Mulyana’s phenomenological approach helped institutionalize interpretive methodologies, emphasizing subjectivity and lived experience. However, this qualitative turn also led to the marginalization of quantitative approaches and generated other disciplinary consequences that remain underexplored. This study explores the long-term impact of the mainstreaming of qualitative approaches on Indonesian communication scholarship by employing a multi-perspectival approach, combining intellectual history, biographical analysis, and autoethnography. This study contributes to the sociology and history of communication studies by highlighting how political transitions, academic authority, and institutional structures shape disciplinary evolution.